The Mechanism and Diagnosis of Insulation Deterioration Caused by Moisture Ingress into Oil-Impregnated Paper Bushing - Bo Qi; Quanmin Dai; Chengrong Li; Zipeng Zeng; Mingli Fu; Ran Zhuo (Energies, 2018)
The healthy state of insulation in oil-impregnated bushings is traditionally evaluated by tanδ and capacitance at power frequency and mostly at 10 kV in the test standard. However, there has frequently been insulation accidents induced by moisture ingress (MI) for bushings that have passed the standard. The mechanism and new diagnostic features for MI into bushings were not distinct enough and an accurate test method is urgently needed research. To address this technical gap, a bushing model with a transparent sheath was designed and an ultrasonic humidifier device was adopted to simulate the environment of MI in bushings and recorded by digital camera. The parameters of dielectric dissipation factor, capacitance, partial discharge (PD), frequency domain response, and moisture content in oil were measured at room temperature with time. The results presented that both the increment dissipation factor at low frequency of 0.001 Hz and the increment dissipation factor of 1.2 Um could be used for detecting the earlier insulation defect of oil-impregnated paper (OIP) bushings. The phase resolved partial discharge (PRPD) can serve as the diagnostic basis of the severe state (S3) of insulation deterioration caused by MI into bushings around the phases of 0–117°, 151–303°, and 325–360°. The research findings would provide a useful reference for the condition diagnosis and maintenance of OIP bushings. Especially, the increment detection of Frequency Domain Spectroscopy (FDS) at the frequency of 1 mHz and 10 kHz was recommended firstly for the operative bushings in real sites.